Penggunaan Aplikasi Solite kids Game untuk Meningkatkan Perkembangan Kognitif Pada Anak Usia 5-6 Tahun - Zaharah, Siti; Herwina, Herwina; Herlinda, Susi (PT. Riset Press International, 2026)
This quantitative experimental study aims to analyze the effect of the Solite Kids Game application on the cognitive development of 5–6 year old children at Umma Zahra Kindergarten, who were previously identified as having difficulties in recognizing number and letter symbols. Through testing of 15 samples using a pre-test and post-test design processed with a paired sample t-test (SPSS), a significant increase in the average value of cognitive development was found from 16.27 to 25.60. The results of the hypothesis test showed a significance value of 0.000 < 0.05 and a t-count value of 11.377 > t-table 2.144, so it can be concluded that the use of the Solite Kids Game application effectively improves children's cognitive abilities significantly, especially in the aspect of symbolic thinking abilities. It is recommended to integrate the Solite Kids Game application as an interactive learning medium to optimize children's cognitive aspects through appropriate guidance, so that play activities remain directed and educational according to their developmental stage.